إسهامات المسؤولية الاجتماعية في تعزيز سلوكيات المواطنة في منظمات الأعمال تجربة شركة Nca رويبة - شيخ, عبد القادر; العمري, اصيلة (جامعة الوادي University of Eloued, 2019)
هدف من خلال هذه الدراسة إلى تسليط الضوء على مساهمة المسؤولية الإجتماعية في تعزيز سلوكيات المواطنة في منظمات الأعمال التي أصبحت ضرورة حتمية في ظل التغيرات الحديثة التي لا تقتصر فيها قيمة المؤسسة على أدائها المالي، من خلال الوقوف واقع ممارسات المسؤولية الاجتماعية في شركة NCA رويبة ومعرفة مدى تأثيرها على المجتمع وقد تم التوصل إلى العديد من النتائج نذكر منها: أنه رغم أن تولي شركة NCA رويبة لتبني المسؤولية الاجتماعية في أعمالها وممارساتها، من خلال توفيرها لفرص عمل معتبرة وبذلك تساهم في تخفیض نسبة البطالة وكذلك تساهم في نشاطات منظمات المجتمع المدني وتحرص على توفیر الرعایة الصحیة والاجتماعیة للعمال ولعائلاتهم . In this study we aim to shed light on the contribution of social responsibility to the promotion of citizenship behaviors in business organizations, which have become imperative in light of the recent changes in the value of the institution to its financial performance by standing the reality of social responsibility practices in NCA Ruwaiba Impact on society A number of conclusions have been reached: NCAA is responsible for the adoption of social responsibility in its work and practices by providing significant employment opportunities, thereby reducing unemployment, contributing to the activities of civil society organizations and ensuring the provision of health and social care to workers. And their families.
Contributions to social responsibility in promoting citizenship behaviors in business organizations Experience of NCA Ruwaiba Company
مقال
Keywords: المسؤولية الاجتماعية، مواطنة منظمات الأعمال، المسؤولية الأخلاقية; Keywords: social responsibility, citizenship of business organizations, ethical responsibility